Direct in vitro regeneration of castor bean plants (Ricinus communis) using epicotyls (Bioscience Journal, 2019)
A regeneration protocol for castor bean plant (Ricinus communis) was successfully developed using epicotyl sections obtained from in vitro seedlings. The maximum number of induced shoots (4.3 shoots/explant) and highest shoots frequency (75,56%) was obtained in WPM medium supplemented with TDZ (1 mg/L) and zeatin (0.5 mg/L), whereas the minimum number (0.8 shoots/explant) and lowest shoots frequency (37,78%) was obtained in medium containing TDZ (1 mg/L) and BAP (0.5 mg/L). The highest percentage of rooting (93.3%) was obtained in a medium containing IBA (1 mg/L). These plants were transplanted in a mesh house and achieved a high adaptability to acclimatization, reaching 77% survival. On the other hand, the maximum elongation (height) during this stage was 7.9 cm in plants supplemented with WPM nutrients, whereas it was only 4.38 cm in control plants.